Perlindungan Hukum Kepada Konsumen Yang Dirugikan Atas Pembelian Masker Kain Kesehatan Yang Tidak Ber-Standar Nasional Indonesia (SNI) - Finda Romadhona (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2022)
The overall policy on the use of masks has been the subject of extensive debate since the early stages of the COVID-19 pandemic. Insufficient supply of surgical masks has forced the public and the government to allow the use of cloth masks. With the stipulation of SNI 8914:2020 regulations, the quality requirements for masks made of woven fabrics and/or knitted fabrics from various types of fiber, consist of at least 2 (two) layers of fabric and can be washed several times (washable). Business actors who trade cloth masks that do not comply with the rules that have been set so that this causes harm to consumers. In order to realize the rights of consumers who have been harmed, legal protection is needed for these consumers in accordance with Law Number 8 of 1999 concerning Consumer Protection. The research method used is normative or doctrinal research, which is a type of research that focuses on examining the application of rules or norms in positive law. The results of the study conclude that if there are consumers who buy and use cloth masks that do not have the Indonesian National Standard (SNI) then business actors are obliged to provide accountability. Accountability given by business actors to the products produced must be in accordance with the principle of product responsibility which is known in the legal world, especially business. The responsibility is carried out because it has violated the rights of consumers as described in Article 4 of Law Number 8 of 1999 concerning Consumer Protection letter a